Structure-based virtual screening identified novel FOXM1 inhibitors as the lead compounds for ovarian cancer - Zhou, Zi-Ying; Han, Xiao-Yang; Sun, Lian-Qi; Li, Si-Yan; Xue, Si-Tu; Li, Zhuo-Rong (Frontiers in Chemistry, 2022)
Ovarian cancer (OC) is a gynecological tumor with possibly the worst prognosis, its 5-year survival rate being only 47.4%. The first line of therapy prescribed is chemotherapy consisting of platinum and paclitaxel. The primary reason for treatment failure is drug resistance. FOXM1 protein has been found to be closely associated with drug resistance, and inhibition of FOXM1 expression sensitizes cisplatin-resistant ovarian cancer cells. Combining existing first-line chemotherapy drugs with FOXM1 prolongs the overall survival of patients, therefore, FOXM1 is considered a potential therapeutic target in ovarian cancer. Previous research conducted by our team revealed a highly credible conformation of FOXM1 which enables binding by small molecules. Based on this conformation, the current study conducted virtual screening to determine a new structural skeleton for FOXM1 inhibitors which would enhance their medicinal properties. DZY-4 showed the highest affinity towards FOXM1, and its inhibitory effect on proliferation and migration of ovarian cancer at the cellular level was better than or equal to that of cisplatin, while its efficacy was equivalent to that of cisplatin in a nude mouse model. In this study, the anti-tumor effect of DZY-4 is reported for the first time. DZY-4 shows potential as a drug that can be used for ovarian cancer treatment, as well as a drug lead for future research.